A Variant of Projection-Regularization Method for ill-posed linear operator equations - Bechouat Tahar; Boussetila Nadjib; Rebbani Faouzia (International Journal of Computational Methods, 2020)
In the present paper, we report on a strategy for computing the numerical approximate solution for a class of ill-posed operator equations in Hilbert spaces: Kf = g. This approach is a combination of Tikhonov regularization method and the finite rank approximation of K. Finally, numerical results are given to show the effectiveness of this method.